Psychological Aspects Of Learning In The Virtual Environment - Lukashenko, Irina; Lutsenko, Olena (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
The article of I. Lukashenko, O. Lutsenko “Psychological aspects of learning in the virtual environment”is aimed to analyze psychological aspects of people learning and functioning in the virtual environment. There were analyzed a number of researches which highlight such psychological aspects of people’s functioning in the virtual environment as motivational, cognitive, age-related, pedagogical, social, clinical, gender, psychophysiological and other ones. There are several advantages of Internet-learning in compare with traditional one – decrease of pedagogical authoritarianism, increase of learners independence, their higher responsibility for their learning, expanding the boundaries of learning, time economy etc. At the same time the Internet is characterized by specifis, which may make potential threats to the successful learning in it. These include addictions forming, identity violations, problems with the information defense, deterioration of communication quality, the development of deviations and specifi psychopathology. Interaction with psychologists is desired during the development of distance learning courses to improve their effiiency and for its implementation at the time of appearing above mentioned problems.